Functional and radiological outcome of wedgeless ‘V’ osteotomy for genu valgum in adolescents: a prospective cohort study - Singh, Simran Preet; Gupta, Pallav; Choudhary, Aamir (International Journal of Research in Medical Sciences, 2021)
Background: Genu valgum, commonly called "knock-knee, is a coronal plane angular deformity of knee, which is a common disorder affecting children and adolescents. Distal femoral wedgeless V osteotomy is one of the various methods of treating genu valgum. Methods: A prospective cohort study was conducted between July 2017 to March 2020 in Govt Medical College, Jammu on 28 patients of genu valgum with femoral deformity. A wegdeless V osteotomy was done at the supracondylar level and fixed with K wires. The results were compaired on the basis of radiological parameters such as TFA and MAD. IMD was also compared. The functional outcome was evaluated using Bostman knee score at 6 months of follow-up. 1 patient was lost in follow up and was not included in the study. Results: 27 patients were included in the study with a mean age of 17.5 years (range 15-21 years). The radiological parameters such as TFA showed improvement from a mean of 20.71 to 5.87 postoperatively. IMD decreased from a mean of 13.77 cm to 3.69 cm and MAD from 18.76 mm to 3.03 mm. The functional assessment was made using Bostman score with a mean of 27.1 at final follow up. Conclusions: Supracondylar wedgeless V-osteotomy is an excellent technique for correction of the genu valgum deformity in the adolescent. The learning curve, surgical exposure, and surgical time being minimal. Sparse complications have been reported with this technique as compared to the other type of osteotomies.